Comparative analysis of formulation buffers and storage temperatures on stability of a novel, recombinant multi-epitope peptide vaccine against COVID-19 - Singh, Alok; Kumar, Prevesh; Diksha, Diksha; Verma, Navneet (Journal of Neonatal Surgery, 2025)
Background: Formulation of therapeutic proteins is of utmost importance for their stability and biological activity. Protein-based vaccines also require optimal formulation for long term storage, transport and usage. Various analytical studies are performed to evaluate the stability of vaccines over a time period at different storage temperatures. Objectives: The present study provides a comparative analysis of the stability of a novel multi-epitope COVID-19 vaccine in three different formulation buffers and two different storage temperatures. Methods: Three different formulation buffers were prepared by addition of different adjuvants (FB01, FB02 and FB03). According to the International Conference on Harmonization (ICH- Q5C) guidelines, real-time and accelerated stability studies were carried out to determine the stability of the novel vaccine candidate at two storage temperatures – +2–8 ºC (real-time, up to 6 months) and +25 ºC (accelerated, up to 1 month). Results: The stability assessment showed that the recombinant multi-epitope peptide vaccine was more stable at +2–8 ºC storage temperature in all three buffers tested as compared to when stored at +25 ºC. Conclusion: The study reports that formulation buffer, FB01, is the most preferred buffer for maintaining the stability of the peptide vaccine at +2–8 ºC for 6 months.